The Historical Present in the Lithuanian Novel In the Shadow of the Wolves, by Alvydas Šlepikas, and Its Translation into Spanish - Caro Dugo, Carmen (Verbum, 2025)
This paper explores a stylistic feature of the Lithuanian novel Mano vardas - Marytė (translated into English as In the Shadow of Wolves) and its translation into Spanish (Bajo la sombra de los lobos). The use of the present tense in the Lithuanian text imbues the narrative with vitality and dynamism, engaging the reader in the events described. The interplay of the historical present tense with retrospective past tenses provides clarity to the sequence of events and serves as a dramatizing resource for the events narrated in the present. Though the present tense can also be used in Spanish in a similar way, the translator has chosen to transfer the reader to a past tense. A comparison of selected passages from the original text with their translation shows that the translated text establishes more distance from the events narrated, the time sequence becomes less distinct and the narration loses dynamism.
Keywords: translation from Lithuanian; historical present tense; temporal sequence; narrative dynamism